Exploring the Dissemination and Strategies of Current Affairs journalism on Integrated Media Platforms - Cui, Yue (International Journal of Social Sciences and Public Administration, 2024)
This article aims to delve into the impact of integrated media platforms on the dissemination of current affairs journalism and the strategic mechanisms behind it. It provides an in-depth analysis by first defining the concept of integrated media platforms and distinguishing them from traditional media, highlighting their unique characteristics. Subsequently, through real-world case studies, the article explores the strategies employed for disseminating current affairs journalism across different platforms and evaluates their effectiveness. It further discusses the challenges related to social impact and public opinion management, offering recommendations for guiding and managing public opinion. This research aims to provide a comprehensive understanding of the role of integrated media platforms in current affairs journalism dissemination, offering theoretical support and practical guidance for related studies and practices.